Republic of Armenia : Report on the Observance of Standards and Codes; Data Module, Response by the Authorities, and Detailed Assessment Using the Data Quality Assessment Framework (DQAF). (IMF Staff Country Reports; Country Report ;, 2009)
This paper presents the Republic of Armenia's report on the Observance of Standards and Codes and detailed assessment using the data quality assessment framework. Armenia exceeds Special Data Dissemination Standard requirements for both periodicity and timeliness in releases of data on unemployment, general government operations, analytical accounts of the central bank, merchandise trade, international investment position, and population. Armenia meets periodicity and exceeds timeliness on production index, employment, wages, consumer price index, producer price index, central government operations, analytical accounts of the central bank, and merchandise trade.